Proceso de ASC - ESTUDIO DEL CICLO DE VIDA Y DISPOSICION FINAL DE BATERIAS DE VEHICULOS ELECTRICOS-FASE EXPLORATORIA (2020)
The high levels of air pollution that have been documented in recent years in the country's main urban areas, consistent with global patterns, have prompted national authorities to consider tax incentives for mobility options that encourage environmentally friendly practices. These measures are designed to not only mitigate existing air pollution but also promote sustainability. As a result, there has been a significant increase in the purchase of electric vehicles. According to Andemos Colombia, as of January 31, 2019, there are 2,826 electric cars and motorcycles in Colombia, including 1,048 cars and 1,778 motorcycles, which is just 0.02% of the total 14,104,129 vehicles in the national fleet. However, some concerns focus on the future, as without proper planning, one problem could be replaced by another, or even worsen. Batteries, which are essentially chemical systems for energy production, are made of materials that can be difficult to recycle without the proper disposal processes, potentially leading to significant soil and water pollution in the future. This concern has raised questions such as: What will be done with the batteries from electric vehicles when they need replacement? How will they be recycled? What processes are necessary for the environmentally responsible disposal of these batteries? Therefore, the materials research group aimed to investigate the composition of these batteries more deeply and explore recycling methods to prevent further environmental damage.